Assessing the Success of the Holistic Early Childhood Program in Semarang Merak’s Cluster - Wasilaturrohmah, Siti; Rochmawati, Nur Intan (Al Hikmah: Journal of Education, 2024)
The Holistic Integrative Early Childhood Development (PAUD HI) program addresses the multidimensional needs of young children, integrating education, health, nutrition, and protection. This study aims to evaluate the implementation and outcomes of the PAUD HI program in the Merak Cluster, West Ungaran District, Semarang Regency. Using a qualitative research approach, data were collected through observations, in-depth interviews, and document analysis involving educators, parents, and institutional stakeholders. The study employed the Miles and Huberman framework for data analysis, focusing on data reduction, display, and conclusion drawing. Triangulation methods ensured the validity and reliability of findings. Results showed high parental engagement, effective health monitoring, and well-implemented nutrition programs, despite challenges in resource availability and educator training. The program successfully integrated multi-stakeholder collaboration to enhance child development. It concludes that the PAUD HI program serves as a replicable model for holistic early childhood education, with actionable insights for future policy and program improvement.